A Study about Impacts of China’s Universal Two-child Policy on Chinese Professional Women - Hao, Ying (My University, 2021)
The thesis studies China’s Universal Two-child Policy (全面二孩政策) from the perspective of Chinese professional female, as it tries to examine the impacts of the new population policy on Chinese professional women’s family life and career development. This empirical work wants to give voice for Chinese female, and raise more attention to their rights under the new social policy background. The survey data was collected by online interviews in Beijing between January 2021 and February 2021. There were in total 23 informants, all of them were Chinese nationals between 20 to 48 years old. All the interviews were conducted in the Chinese language. The data gained from the interviews were analyzed in combination with existing literature findings. The Universal Two-child Policy does re-emancipate Chinese women’s reproductive rights to a certain extent, tends to provide more support in family elderly-care, and helps to enhance people’s family happiness level. On the other hand, it leads to adverse effects on the health, economic status and family relationships of most professional women. The two-child policy also intensifies the original invisible employment discrimination, causing pregnancy and childbirth to become main barriers in women’s job-hunting and career promotion. Coupled with the influence of Chinese traditional gender order, and the lack of social support, more and more Chinese professional women are facing dilemmas in both family and society during the two-child era. An in-depth understanding of Chinese professional women’s childbearing willingness and the impacts of the two-child policy on them will help to interpret the changes in China’s fertility level and birth rate, so as to find out practical guidance for the next step in adjusting China’s population policy.
Keywords: China, Universal Two-child Policy, Chinese professional women, interview, gender roles